Hubungan Mekanisme Koping terhadap Stres pada Lansia Penderita Hipertensi - Veratul Amna; Urip Pratama; Iskandar Iskandar; Yadi Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension, or high blood pressure, is a medical condition characterized by a persistent increase in blood pressure exceeding normal thresholds. The aim of this study was to examine the relationship between coping mechanisms and psychological stress among elderly individuals with hypertension in Meunasah Papeun Village, Krueng Barona Jaya District. This research employed a quantitative design with a descriptive-analytic approach using the Cross-Sectional Study method. The total population consisted of 77 participants, and the sampling technique utilized total sampling. The study was conducted from June 25 to July 16, 2025. Data collection instruments included the Brief Cope questionnaire and a stress questionnaire developed by the researcher, with a reliability value of Cronbach’s alpha P-Value = 0.693. Data analysis was carried out using the Chi-Square test. The study findings revealed a P-Value = 0.503 (>0.05), indicating no significant relationship between coping mechanisms and stress among elderly individuals with hypertension in Gampong Meunasah Papeun. Respondents are advised to maintain emotional stability to prevent psychological stress; although the findings indicate no direct correlation, it remains essential to preserve mental well-being through effective communication, participation in positive activities, and seeking family support. The village as the research site is encouraged to continue developing stress reduction programs through educational and preventive approaches, such as counseling on coping mechanisms for stress and group discussions.